Perioperative Outcomes for Laparotomy Compared to Robotic Surgical Staging of Endometrial Cancer in the Elderly: A Retrospective Cohort. Issue 9 (1st November 2016) - Backes, Floor J.; ElNaggar, Adam C.; Farrell, Michael Ryan; Brudie, Lorna A.; Ahmad, Sarfraz; Salani, Ritu; Cohn, David E.; Holloway, Robert W.; Fowler, Jeffrey M.; O'Malley, David M.
Abstract : Objective: This study aimed to compare outcomes of endometrial cancer (EMCA) staging in elderly patients performed either robotically or via laparotomy. Methods: A retrospective, multi-institutional chart review was conducted of all robotic and laparotomy staging surgeries for EMCA between 2003 and 2009. Charts were reviewed for intraoperative and postoperative complications and morbidities. Results: Seven hundred forty-six women were identified who had undergone EMCA staging either robotically or via laparotomy; 89 and 93 patients 70 years or older underwent staging for EMCA via robotic and laparotomy, respectively. Both groups had similar age and body mass index. Among elderly patients being staged robotically, a higher incidence of pelvic lymphadenectomy, and decreased blood loss, incidence of blood transfusion, and overall complications were seen compared to laparotomy. Postoperatively, elderly patients staged robotically had a shorter median hospital stay (1 vs 4 days, P < 0.001), with no increase in readmission or return to the operating theater. No vessel, bowel, or genitourinary injuries occurred. Vaginal cuff dehiscence after robotic surgery was not significantly different, but wound and fascial complications were significantly increased in patients undergoing laparotomy. Thromboembolism rates were similar between both groups. Conclusions: Elderly patients can safely undergo robotic EMCA staging with improved outcomes compared to laparotomy. The benefits of robotic staging include higher incidence of completion of lymphadenectomy, decreased hospital stay (without an increase in readmissions or reoperations), decreased transfusions, and decreased wound and fascial complications.